SAGO STARCH COMPRESSING MACHINE: INCREASING THE PRODUCTIVITY WITH NEW CONCEPT - Farihana A.Rahman; Syarfadila Ezurida Shaari; Brenda Anak Norbert Rabar, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Sago is the staple food of Melanau in Sarawak. Sago is sourced from Pokok Rumbia or known as Pokok Sagu which is widely found in the interior of the forest. Pokok Rumbia is a kind of palm tree found in Malaysia and Indonesia forests. Among the products of sago trees is wet sago starch or ‘Lemantak’. Wet sago starch is still traditionally produced by Small and Medium Enterprises (SMEs). By utilizing the compressed air produced using the single-acting cylinder from a pneumatic system, the sago starch is compressed with 1.5 horsepower. Through careful selections of concepts, the final selected concept was fabricated and analysed. Machine efficiency analysis is determined by taking into account the compressor pressure factor, the time taken for compression, the height of wet sago starch, and the rate of production at a given time. It is proven that with the implementation of the process through the new machine concept, the productivity of ‘Lemantak’ has increased by 68% compared to the conventional method of production.